Experiences of Adolescents on Antiretroviral Therapy at Rustenburg Sub-District, Northwest Province, South Africa - Happy Maybe Maambiwa Khangale; Ndidzulafhi Selina Raliphaswa; Azwidihwi Rose Tshililo (MDPI AG, 2024)
Background: Antiretroviral therapy (ART) is the treatment of people infected with human immunodeficiency virus (HIV) using anti-HIV drugs. The standard treatment consists of a combination of drugs (often called highly active antiretroviral therapy or HAART) that suppress HIV replication. As a result, people who have been infected live longer while on ART, which was initiated in South Africa in 2004. Aim: The study aimed to explore the experiences of adolescents on antiretroviral therapy in two primary health care clinics in Rustenburg sub-district Northwest Province. Methods: Qualitative, explorative, descriptive, and contextual approaches were adopted. Non-probability purposive sampling was used to select the healthcare facilities, and adolescents were chosen using convenience sampling. In-depth individual interviews were used to collect data from the participants. Only 13 adolescents between the ages of 15 and 19 years were interviewed. Collected data were analyzed using Tesch's eight steps. Results: Qualitative themes identified included a description of the experiences of adolescents living HIV to adulthood and challenges experienced from childhood to adolescence period. Each theme had different sub-themes which included the paradoxical experiences of being diagnosed with HIV and being on antiretroviral treatment. Adolescents experienced poor adherence to ART due to treatment side effects such as drowsiness, change in body image, and headaches. Self-stigma resulted in adolescents not disclosing their status to their peers, closest and sexual partners which also made them not to adhere well in treatment. Conclusions: The study findings revealed that HIV-positive adolescents encounter various experiences while on ART, which causes them not to adhere to treatment. In the study, adolescents also experienced self-stigma which also affected their treatment adherence and brought fear of losing their loved ones.